An international framework to discipline outward FDI incentives? - Karl P. Sauvant; Clémence Boullanger (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
As more countries report outward FDI, home country support for outward FDI is becoming more common. This Perspective argues that any home country assistance should focus on projects with domestic benefits, and proposes discussions on an international outward FDI-incentives agreement to avoid wasteful incentive competition between countries.
Keywords: 330